PRODUÇÃO DE TEXTOS NO LIVRO DIDÁTICO DE ALFABETIZAÇÃO: ANÁLISE DOCUMENTAL EM DIÁLOGO COM PROFESSORAS ALFABETIZADORAS - Pires, Renata Luchi (2021)
The work integrates studies developed in the field of language, in an enunciative- discursive approach, in the Educational practices, diversity and inclusion research line, of the Post-Graduation Program of Professional Masters in Education at the Federal